عزل وتشخيص الأنواع البكتيرية من ريش نوعين من طيورالبط المدجنة في محافظة البصرة - عبد الجبار السلمي, أمين; حسن وداعه, قاسم (University of Thi-Qar Journal of Science, 2010)
This research deals with the isolation of bacteria from aquatic birds mallard(Anas platyrhynchos ) (5 male and 10 female) and pintail (Anas acuta)(3male and7 female).Atotal 25 birds have been collected from different locations fromBasrah province and identification for 18 species of bacteria children1- Serratia Plymuthica 2- Enterobacter sakazakii 3-- Clostridium histolyticum4- Staphylococcus saprophyticus 5- Pseudomonas aeruginosa 6- E.coli 7- Pseudomonas diminuta 8- Kluyvera ascorbata 9- Citrobacter braakii 10- Klebsella oxytoca 11- Serratia ficaria 12-Proteus mirabilis 13- Provdencia stuartii 14- Aeromonas hydrophila 15- Bacillus firmus 16- Citrobacter freundii 17- Citrobacter diversus 18- Staphylococcus sciuri The data analysis T.test and the correlation coefficient between weight increase and bacteria percentage and significant at level p<0.05 there were no significant difference 0f bacteria species according to the birds sex.